Multilateral Governance and Conflict Resolution: Pathways to Sustainable Peace - Bernardianto, R. Biroum (Politeia : Journal of Public Administration and Political Science and International Relations, 2025)
This study provides a comprehensive narrative review of multilateral governance and its role in conflict resolution, focusing on global and regional mechanisms of peacebuilding and security. The objective was to examine how international and regional organizations address complex security challenges and to identify the systemic barriers that constrain their effectiveness. A systematic methodology was applied, drawing on peer-reviewed studies retrieved primarily from Scopus and Web of Science using key terms such as "security governance," "conflict resolution," "multilateralism," "regional security," and "peacebuilding." Inclusion criteria emphasized peer-reviewed publications from the last decade, with a focus on empirical and applied analyses. The findings reveal that international organizations such as the United Nations and NATO provide essential but distinct approaches to peacekeeping, while regional bodies like the African Union, ASEAN, and IGAD offer contextualized frameworks rooted in local realities. Social and economic factors, including resource governance, trade interdependence, and civil society participation, significantly enhance legitimacy and sustainability. Technological innovation, particularly big data and artificial intelligence, presents promising tools for conflict prevention, yet disparities in access perpetuate inequalities. Systemic barriers such as political fragmentation, structural imbalances, and disinformation continue to undermine multilateral efforts. The discussion emphasizes the importance of adaptive governance, inclusivity, and hybrid frameworks that integrate international oversight with local participation. The study concludes that multilateral approaches remain indispensable for addressing global security challenges. Policies should prioritize institutional capacity-building, inclusive governance, and digital resilience, while future research should explore hybrid models and interdisciplinary perspectives to strengthen sustainable conflict resolution.